Creative Thinking Processes in Contextual Problem Posing Based On Adaptive And Innovative Cognitive Styles - Masriyah; Ali Shodikin; Anggita Auni (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2026)
This study aims to describe the creative thinking processes of junior high school students in posing contextual mathematical problems of social arithmetic material with cognitive styles. A qualitative descriptive approach was employed. The subjects were two eighth-grade students with equivalent mathematical abilities but different cognitive styles, identified through a cognitive style questionnaire and a mathematics ability test. Data were collected using post-solution problem-posing tasks, video-based observations, and semi-structured interviews. The analysis focused on students’ creative thinking processes with indicators of fluency, flexibility, and originality through four stages: preparation, incubation, illumination, and verification. The findings show that both adaptive and innovative students experienced all stages of the creative thinking process. In the preparation stage, students were able to understand and solve the initial problem. During incubation, ideas emerged from the given information, prior knowledge, and personal experiences, accompanied by revisions of initial ideas. In the illumination stage, both students demonstrated fluency and flexibility in posing contextual problems, while originality appeared in problems that modified perspectives or objectives beyond routine calculations. Differences were observed in the characteristics of the posed problems. The adaptive student tended to develop problems within existing structures, whereas innovative student was more inclined to modify conditions and generate less structured problems. In the verification stage, both students rechecked the logic, numerical accuracy, and solutions of the posed problems. These findings indicate that there are differences in the characteristics of students' creative thinking processes in posing contextual mathematical problems in different cognitive styles.